2015
DOI: 10.1038/nature14105
|View full text |Cite
|
Sign up to set email alerts
|

Impact jetting as the origin of chondrules

Abstract: Chondrules are the millimetre-scale, previously molten, spherules found in most meteorites. Before chondrules formed, large differentiating planetesimals had already accreted. Volatile-rich olivine reveals that chondrules formed in extremely solid-rich environments, more like impact plumes than the solar nebula. The unique chondrules in CB chondrites probably formed in a vapour-melt plume produced by a hypervelocity impact with an impact velocity greater than 10 kilometres per second. An acceptable formation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
182
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(201 citation statements)
references
References 41 publications
18
182
0
Order By: Relevance
“…This implies that multiple chondrule formation mechanisms were operating in distinct regions of the protoplanetary disk. The high surface densities and high-energy environments typical of the inner protoplanetary disk may provide a regime for chondrule formation through shock-related transient heating events (55), whereas chondrule formation in the outer Solar System may occur via impacts and bow shocks (56)(57)(58). Therefore, comets are still the best candidates to provide insights into the composition of the primordial interstellar matter parental to our Solar System.…”
Section: Origin Of High-temperature Cometary Componentsmentioning
confidence: 99%
“…This implies that multiple chondrule formation mechanisms were operating in distinct regions of the protoplanetary disk. The high surface densities and high-energy environments typical of the inner protoplanetary disk may provide a regime for chondrule formation through shock-related transient heating events (55), whereas chondrule formation in the outer Solar System may occur via impacts and bow shocks (56)(57)(58). Therefore, comets are still the best candidates to provide insights into the composition of the primordial interstellar matter parental to our Solar System.…”
Section: Origin Of High-temperature Cometary Componentsmentioning
confidence: 99%
“…At that time, however, it was thought that collisions did not play an important role in forming chondrules, because the outcome of collisions is fragmentation of the colliding bodies, rather melting them. One of the new findings made by Johnson et al (2015) is that, when planetesimals collide with each other, some melted materials can be ejected from their collisional surface. This process is referred to as impact jetting and was indeed suggested by Sanders & Scott (2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently recognized that none of them can fully reproduce the wealth of chondrules' properties. Johnson et al (2015) have recently performed a series of numerical simulations and shown that collisions among planetesimals and the resultant impact jetting may be a plausible candidate to form chondrules. It is interesting that the idea of planetesimal collisions was initially proposed in the 1960s (e.g., Urey & Craig 1953).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the origin of chondrules remains poorly understood, and a wide range of possible formation mechanisms has been proposed: (i) chondrules may have formed through collisions between protoplanetary bodies (4-6); (ii) chondrules may have formed near the Sun and were then transported outward by protostellar jets (7); and (iii) chondrules may have formed through more localized melting events of nebular dust caused by shock waves (8,9) or current sheets (10). Although many recent models argue for an impact origin of chondrules (4)(5)(6), the observation that chondrules and matrix from carbonaceous chondrites are chemically complementary lends strong support to an origin of both components from a single reservoir of nebular dust (11)(12)(13). However, the significance of this chemical chondrule-matrix complementarity and whether it can distinguish between a nebular or impact origin of chondrules is debated (6).…”
mentioning
confidence: 99%